2003
DOI: 10.1074/jbc.m304387200
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Bordetella pertussis Adenylate Cyclase with CD11b/CD18

Abstract: Adenylate cyclase toxin (CyaA) is one of the major virulence factors produced by Bordetella pertussis, the whooping cough agent. CyaA belongs to the repeat in toxin protein family and requires a post-translational fatty acylation to form cation-selective channels in target cell membranes and to penetrate into cytosol. We have demonstrated recently that CyaA uses the ␣ M ␤ 2 integrin (CD11b/CD18) as a specific cellular receptor. Here we show that the acylation of CyaA is required for a productive and tight inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
60
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 115 publications
(61 citation statements)
references
References 44 publications
0
60
0
1
Order By: Relevance
“…However, intriguingly enough, CyaA appears to bind CD11b/ CD18 in a way that by itself does not promote any calcium entry into cells. This is best documented by the inability of the CyaA-⌬AC or CyaA-247LQ mutants to elicit calcium entry into J774A.1 cells, despite their fully conserved capacity to tightly bind CD11b/CD18, to penetrate cellular membranes, deliver the AC domain (CyaA-247LQ), and form the hemolytic pores (6,47,59,64).…”
Section: Discussionmentioning
confidence: 99%
“…However, intriguingly enough, CyaA appears to bind CD11b/ CD18 in a way that by itself does not promote any calcium entry into cells. This is best documented by the inability of the CyaA-⌬AC or CyaA-247LQ mutants to elicit calcium entry into J774A.1 cells, despite their fully conserved capacity to tightly bind CD11b/CD18, to penetrate cellular membranes, deliver the AC domain (CyaA-247LQ), and form the hemolytic pores (6,47,59,64).…”
Section: Discussionmentioning
confidence: 99%
“…We also showed recently that a region essential for CyaA binding to its cellular CD11b/CD18 (␣ M␤2 integrin) receptor encompasses a non-RTX segment between the RTX block II and block III motifs. Calcium-induced conformational rearrangements of this segment might explain the strict calcium dependence of the CyaA/CD11b association (31).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been demonstrated that CyaA binds specifically to target cells through the ␣ M ␤ 2 integrin receptor (CD11b/CD18) (30,31), which is expressed on a restricted subset of leukocytes including neutrophils, macrophages, and dendritic cells. Expression of this receptor most likely accounts for the high sensitivity of these cells to CyaA (13,30).…”
mentioning
confidence: 99%
“…Thus, the basolateral membranes of polarized T84 cells allow translocation even under depolarized conditions. Post-translational, covalent acylation by the acyl-transferase CyaC is required for hemolytic activity and for fully functional translocation/intoxication by ACT, although it is not required for in vitro enzymatic activity (13,25,(43)(44)(45). J774 cells express CD11b/CD18 and are intoxicated by nonacylated ACT, but with a 50-fold reduction in toxin potency.…”
Section: Rapid Induction Of I Sc By Act At the Basolateral Surface Bumentioning
confidence: 99%